Analisis Penggunaan Media Sosial Sebagai Alat Pemasaran Oleh Usaha, Mikro, Kecil Dan Menengah (Umkm): Perspektif Pengusaha Dan Konsumen - Tate Agape Bawana (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2025)
This study aims to analyze the use of social media as a marketing tool by Micro, Small and Medium Enterprises (MSMEs) from the perspective of entrepreneurs and consumers. Social media has become an important platform for MSMEs to promote products, build brand awareness, and establish closer interactions with consumers. This research uses a literature review method that aims to explore and analyze various studies and articles related to the use of social media by MSMEs as a marketing tool. The results show that social media contributes significantly to increasing business visibility, sales, and customer loyalty. However, MSME players face challenges such as limited knowledge of digital marketing, time management, and campaign effectiveness measurement. This study suggests the need for digital training and consistent content management to maximize the potential of social media in marketing.